Understanding the hydration of arylacetylenes to synthesize the carbonyl compounds via electroreduction of bromide intermediates. (25th April 2023) - Yuan, Hongyan; Ji, Mengyuan; Xue, Huimin; Chen, Hongyu; Zhang, Yanhua
Abstract: A deeper understanding of the electrochemical hydration of the alkynes may promote the development of such reactions. By using 4- tert -butylphenylacetylene as the model substrate, the mechanism of the electro-hydration of acetylenes is investigated through the designed experiments and theoretical calculations. It is suggested that the reaction may follow two possible radical processes simultaneously. The major is a cascade pathway including an oxidative halogenation followed by an electrochemical stepwise-dehalogenation, and the minor is the direct hydration of the substrate on the electrode surface. The inference is further confirmed by the corresponding thermodynamic calculations. This mechanistic study provides a theoretical basis for the future design and synthesis of various functionalized aryl ketones from the arylacetylenes by the electrochemistry strategy. Graphical abstract: Image 1